Infrared spectroscopy for a quantitative determination of CH3-nClnCOCl in TiCl4. Issue 1 (November 2015) - Yang, B; Wang, Y; Tan, H; He, J; Song, G
Abstract: Infrared spectroscopy permits a determination of the concentration of CHCl2 COCl, CH2 ClCOCl and CCl3 COCl as the organic impurities in TiCl4 . In this study, an infrared spectrometer with ZnSe window and the cell of PTFE was assembled, and used to determine the concentration of three organic impurities. The detection limits of CCl3 COCl, CHCl2 COCl, CH2 ClCOCl were determined as 3.16×10 -3 μg/g 1.92×10 -3 μg/g and 1.55×10 -2 μg/g respectively. The new method is applied to quality control of refined TiCl4 from titanium sponge.